Inside Back Cover: Isolation of CeLu2N@Ih‐C80 through a Non‐Chromatographic, Two‐Step Chemical Process and Crystallographic Characterization of the Pyramidalized CeLu2N within the Icosahedral Cage (Chem. Eur. J. 29/2015). Issue 29 (13th July 2015) - Stevenson, Steven; Thompson, Hannah R.; Arvola, Kristine D.; Ghiassi, Kamran B.; Olmstead, Marilyn M.; Balch, Alan L.
<x xml:space="preserve">Abstract</x> Non‐chromatographic isolation of fullerene The mixed‐metal endohedral fullerene CeLu2N@C80 was isolated without using HPLC by selective precipitation with MgCl2 followed by removal of residual empty cage and endohedral fullerenes by treatment with silica gel functionalized with amino groups. Crystallographic analysis of CeLu2N@C80 reveals that the Ih‐C80 cage is present with a pyramidalized CeLu2N unit inside. For more details, see the Full Paper by S. Stevenson, M. M. Olmstead, A. L. Balch, and co‐workers on page 10362 ff.